Peripapillary vessel density in eyes with cone-rod dystrophy - Shinozuka, Masato; Arai, Mizuho; Hirayama, Yumeno; Uechi, Yuna; Kawasaki, Shohei; Okawa, Kazuyoshi; Iwashita, Yume; Miyazato, Misa; Hirono, Kazushi; Nakamura, Kentaro; Inoue, Tatsuya; Asaoka, Ryo; et al. (PloS one, 2024)
To compared the vessel density (VD) around the optic nerve head (ONH) in eyes with cone-rod dystrophy (CORD) and healthy control eyes in a sector-wise manner and to investigate the relationship between VD around the ONH and visual function in CORD eyes. Twenty-six eyes in 14 CORD patients and 25 eyes in 25 healthy control subjects were examined. Using OCT angiography images, the VDs in the superficial and deep capillary plexus at the macula (sVDm and dVDm) and those around the ONH in the superior, temporal, inferior and nasal region (VDnh_s, VDnh_t, VDnh_i, and VDnh_n, respectively) were measured for each eye. Patient age, visual acuity (VA) and VDs were then compared between two groups. Moreover, the relationships between VA and the VDs were analyzed using a linear mixed model and AICc model selection. No significant difference in age was seen between the CORD and control groups (p = 0.87, Wilcoxon rank sum test), but the VA was significantly lower in the CORD group (p<0.0001). Both sVDm and dVDm were significantly lower in the CORD eyes than in the control eyes (both p<0.0001). Among VDnh_s, VDnh_t, VDnh_i, and VDnh_n, however, only VDnh_t differed significantly between the CORD and control groups (p = 0.035). Among age, VDnh_t, dVDm, and sVDm, the optimal model for VA included only VDnh_t and dVDm. In addition to the VD in the deep capillary plexus at the macula, the measurement of temporal VD around the ONH might be useful for predicting visual function in eyes with CORD.